Plan de Negocios Bon Appetit - Ariza Hernandez, Marisol (Universidad Antonio Nariño, 2024)
Bon Appetit is a dessert venture that aims to provide delicious and high-quality desserts to the city of Santa Marta, Colombia. The company was founded with the vision of creating a brand that represents the best of Colombian desserts, while incorporating international flavors and trends. This paper will explore the concept and vision behind Bon Appetit, the market analysis and target audience, and the execution of the business plan.